Analysis of burnout and its influencing factors among prison police - Gao, Jin; Du, Xinyang; Gao, Qing (Frontiers in Public Health, 2022)
Abstract Background: Burnout among prison police is an occupational health issue in the field of public health. Although burnout has been a hot issue for decades, there has not been a focus on the specific group of prison police. This study explores the burnout status and its influencing factors among prison police. Methods: The Maslach Burnout Questionnaire – General Survey (MBI-GS) was used to conduct a questionnaire survey among 1,024 prison police. Results: It indicates that emotional exhaustion, negative detachment, and self-efficacy were the most significant dimensions of the burnout among prison police officers. The results of multiple linear regression analysis showed that gender (-0.201, P=8.8958E-11<0.05), workload (-0.441, P=1.6287E-9<0.05), whether they have direct contact with supervisory subjects (-0.394, P=2.1449E-39<0.05), and a sense of organizational support (-0.298, P=3.7182E-7<0.05) were risk factors for burnout in prison police. Conclusions: Burnout among prison officers can be reduced through preferential treatment of prison police, sound organizational mechanisms, and self-improvement of prison police.